2019
DOI: 10.1016/j.omtn.2018.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The Attenuation of Trophoblast Invasion Caused by the Downregulation of EZH2 Is Involved in the Pathogenesis of Human Recurrent Miscarriage

Abstract: Recurrent miscarriage (RM) is currently defined as two or more losses of a clinically established intrauterine pregnancy. Despite years of research, RM continues to be a clinically frustrating challenge for patients and physicians, and its etiology remains poorly understood. Accumulating evidence has suggested that epigenetic modifications are involved in early embryogenesis, and defects in epigenetic patterning contribute to the development of RM. Here, we studied the role of enhancer of zeste homolog 2 (EZH2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 58 publications
3
37
0
Order By: Relevance
“…promotes trophoblast cell invasion, and its downregulation is involved in the pathogenesis of human recurrent miscarriage, 47 but the role of EZH2 in PE has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…promotes trophoblast cell invasion, and its downregulation is involved in the pathogenesis of human recurrent miscarriage, 47 but the role of EZH2 in PE has not been explored.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have indicated that Hh signaling played pivotal roles in the development of placental and pregnant maintenance [27,28]. Besides, in the clinic context, early miscarriage patients have several common traits, including deficient trophoblastic invasion, decreasing thickness of CTB layer, deficient myometrial spiral artery remodeling [16,49,50]. Thus, it rationally prompted us to further explore the underlying relationship between the Shh signaling and recurrent miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of peroxiredoxin2 regulating trophoblast proliferation and apoptosis was decreased in recurrent miscarriage [20]. Enhancer of zeste homolog 2 (EZH2), known as an epigenetic factor that promoted trophoblast invasion, was also downregulated in recurrent miscarriage [21]. Thus, these findings indicated that initiation and progression of recurrent miscarriage is a complex context that involving in multiply signalings and steps dysfunctions on development of trophoblast and placentation.…”
Section: Introductionmentioning
confidence: 88%
“…Previous studies emphasized the similarities between placental and tumor tissues and research mostly progressed in the direction of using the knowledge about trophoblast behavior to better understand tumor behavior [33,34]. In recent years, there have been more and more studies where a certain molecule found to be important for the behavior or targeting of tumor cells has subsequently been associated with the functioning of trophoblasts and gestational diseases [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51]. To bring the reader closer to the premise that the same molecules can mediate tumor and trophoblast behavior, we will discuss some of these studies in the paragraph below.…”
Section: Introductionmentioning
confidence: 99%
“…The overexpression of enhancer of zeste homolog 2 (EZH2) protein (histone methyltransferase) is associated with the aggressiveness of some cancers. In the placenta, it induces trophoblastic invasion and is found at reduced levels in placentas from recurrent miscarriages [37]. The chromatin-remodeling proteins, histone deacetylases (HDACs), are greatly increased in various human cancers and promote their progression.…”
Section: Introductionmentioning
confidence: 99%